Efecto de la temperatura y tiempo de almacenamiento en la crujencia, instrumental y sensorial, de manzana delicia (pyrus malus l.) - Reyes Zavaleta, Bellisa Lisset (2016)
The aim of this study was to determine the effect of temperature and storage time on Delicia apple Crispness measured by instrumental methods (sound) and traditional sensory evaluation. 108 samples stored at refrigeration temperatures (4 ° C and 90% RH) and ambient temperature (25 ° C and 80% RH) were analyzed; for a period of 63 and 23 days respectively. Sensory evaluation was conducted with 12 trained judges using a structured scale 10 cm. Sound peaks (dB) resulting from the bite of the samples by the panelists (SM) and an instrument (SI) with two repetitions for each was measured and the signal-noise ratios (SM-R and SI-R were determined). Fruits stored at 25 ° C significantly lost their Crispness at 19 days, while the fruits stored at 4 ° C showed a significant loss just 63 days. Instrumental sensory measurements were related by polynomial regression model with an adjusted R2 of 90.18% to SM and 87.74% for SI.